The Veterans Aging Cohort Study: observational studies of alcohol use, abuse, and outcomes among human immunodeficiency virus-infected veterans. - Conigliaro, Joseph; Madenwald, Tamra; Bryant, Kendall; Braithwaite, Scott; Gordon, Adam; Fultz, Shawn L; Maisto, Stephen; Samet, Jeffrey; Kraemer, Kevin; Cook, Robert; Day, Nancy; Roach, Diedra; et al. (Alcoholism, clinical and experimental research, 2004)
This article represents the proceedings of a symposium at the 2003 annual meeting of the Research Society on Alcoholism in Fort Lauderdale, FL. The organizers/chairs were Joseph Conigliaro and Amy Justice. The presentations were (1) Introduction, by Joseph Conigliaro and Tamra Madenwald; (2) Alcohol and HIV/AIDS: the importance of integrative and translational research, by Kendall Bryant; (3) Alcohol use and abuse among patients with HIV infection, by Joseph Conigliaro and Stephan Maisto; (4) Severity of comorbid alcohol use/abuse in HIV infection, by Amy Justice and Jeffrey Samet; (5) Estimating the impact of alcohol use on long-term HIV outcomes, by Scott Braithwaite and Amy Justice; (6) Homelessness, drug & alcohol use among HIV+ veterans, by Adam Gordon and Robert Cook; and (7) Hepatitis C & alcohol in the VACS 3 study, by Shawn Fultz and Kevin Kraemer. The symposium concluded with a discussion led and facilitated by Diedra Roach.
Keywords: Aging; Alcohol Drinking; Alcoholism; Animals; Cohort Studies; HIV Infections; Humans; Longitudinal Studies; Military Medicine; Societies, Medical; Treatment Outcome; United States; Veterans